Pemberdayaan UMKM Pembuat Roti dengan Meningkatkan Kapasitas Produksi Melalui Pelatihan Membuat Mesin Mixer Adonan Roti di Desa Banjarkemantren Buduran Sidoarjo - Ikhwanuddin Ikhwanuddin; Bambang Triono; Moh. Shaleh; Sudarso Sudarso; Fadllah Farah Diba; Yayu Sriwahyuni Hamzah; Mirza Elmy Safira; M. Catur Rizky; Atmari Atmari; Mohamad Farid (Jurnal Pengabdian Kepada Masyarakat, 2023)
Along with the development of MSMEs in Banjarkemantren Village, it is necessary to make a breakthrough by increasing productivity. With increased productivity, it can directly increase profits. One of these breakthroughs is by changing the process of manually kneading bread dough into a bread dough kneading process machine in the form of a mixer machine that has a large capacity and is fast and is able to increase the viscosity / viscosity of the dough. With a simple concept of dynamo motor to gear box. From the gear box is connected to a 10 cm pulley and forwarded with a v belt to a 30 cm pulley, so that the dynamo speed can be lowered. The mixer can be modified from the old mixer by opening the other 2 sides for wider reach. From here a simple kneading machine was created that can improve the manual method with the machine so that the production of bread dough can increase.